Growth, Visual Quality, and Morphological Responses of 12 Viburnum Taxa to Saline Water Irrigation - Youping Sun; Ji Jhong Chen; Haifeng Xing; Asmita Paudel; Genhua Niu; Matthew Chappell (HortScience, 2020)
Viburnums are widely used in gardens and landscapes throughout the United States. Although salinity tolerance varies among plant species, research-based information is limited on the relative salt tolerance of viburnum species. The morphological and growth responses of 12 viburnum taxa to saline solution irrigation were evaluated under greenhouse conditions. Viburnum taxa included Viburnum ×burkwoodii, V. cassinoides ‘SMNVCDD’, V. dentatum ‘Christom’, V. dentatum var. deamii ‘SMVDLS’, V. dilatatum ‘Henneke’, V. ×‘NCVX1’, V. nudum ‘Bulk’, V. opulus ‘Roseum’, V. plicatum var. tomentosum ‘Summer Snowflake’, V. pragense ‘Decker’, V. ×rhytidophylloides ‘Redell’, and V. trilobum. A nutrient solution at an electrical conductivity (EC) of 1.3 dS·m−1 (control) or saline solutions at ECs of 5.0 and 10.0 dS·m−1 were applied eight times over a 9-week period. Growth, visual quality, and morphological characteristics were quantified at the 4th week and 8th–9th week to assess the impact of salinity stress on the viburnum taxa. Saline solution irrigation imposed detrimental salinity stress on viburnum plant growth and visual quality, and the degree of salt damage was dependent on the salinity levels of irrigation solution and the length of exposure to salinity stress as well as viburnum taxa. Viburnum ×burkwoodii and V. ×‘NCVX1’ had little foliar salt damage during the entire experiment, except those irrigated with saline solution at an EC of 10.0 dS·m−1 exhibited slight to moderate foliar salt damage at the eighth week. Viburnum dilatatum ‘Henneke’, V. plicatum var. tomentosum ‘Summer Snowflake’, and V. trilobum irrigated with saline solution at an EC of 5.0 dS·m−1 had slight and severe foliar salt damage at the 4th and 8th week, respectively. Plants irrigated with saline solution at an EC of 10.0 dS·m−1 exhibited severe foliar salt damage at the 4th week, and all died by the 8th week. Other viburnum taxa also showed various foliar salt damage, especially at an EC of 10.0 dS·m−1. The shoot dry weights of V. ×burkwoodii and V. ×‘NCVX1’ irrigated with saline solution at ECs of 5.0 and 10.0 dS·m−1 were similar to those in the control at both harvest dates. However, the shoot dry weight of other tested viburnum taxa decreased to some extent at the 9th week. A cluster analysis concluded that V. ×burkwoodii and V. ×‘NCVX1’ were considered the most salt-tolerant viburnum taxa, whereas V. dilatatum ‘Henneke’, V. plicatum var. tomentosum ‘Summer Snowflake’, and V. trilobum were sensitive to salinity levels used in this study. This research may guide the green industry to choose relatively tolerant viburnum taxa for landscape use and nursery production where low-quality water is used for irrigation.